Compact Wideband Dual-Frequency Antenna Based on a Simplified Composite Right/Left-Handed Transmission Line with Hilbert Curve Loading. (27th December 2019) - Li, Tianpeng; Zhang, Jian; Cheng, Baowei; Lei, Xue; Xu, Zhijian; Gao, Jun
Abstract : This paper addresses the issues of low bandwidth, gain, and efficiency of miniaturized microwave antennas by proposing a novel wideband dual-frequency coplanar waveguide antenna design based on a simplified composite right/left-handed (SCRLH) transmission line structure with Hilbert curve loading. The multifrequency characteristics of the SCRLH transmission line structure are evaluated theoretically, and the antenna parameters promoting bandwidth broadening under zeroth-order resonance (ZOR) and first-order resonance (FOR) mode operation are evaluated. The bandwidth broadening in the ZOR and FOR modes is accordingly revealed to be independent of the antenna length, and the structure therefore facilitates wideband operation under miniaturization. Finally, the dual-frequency ZOR and FOR mode antenna design with center frequencies of f 0 = 1.865 GHz and f 1 = 2.835 GHz is validated via simulation, and the performance of a compact prototype antenna is evaluated experimentally. The −10 dB return loss bandwidths at f 0 and f 1 are 187 MHz (from 1.773 GHz to 1.96 GHz) and 368 MHz (from 3.002 GHz to 3.37 GHz), and the corresponding relative bandwidths are 10.1% and 11.5%, respectively. The experimentally measured peak gains and radiation efficiencies at f 0 are 1.54 dB and 81.3%, respectively, and those at f 1 are 1.71 dB and 74.2%, respectively.